2000
DOI: 10.1016/s0002-9440(10)64602-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Matrix Metalloproteinase Activity Attenuates Tenascin-C Production and Calcification of Implanted Purified Elastin in Rats

Abstract: Elastin, a major extracellular matrix protein present in arterial walls provides elastic recoil and resilience to arteries. Elastin is prone to calcification in a number of cardiovascular diseases including atherosclerosis and bioprosthetic heart valve mineralization. We have recently shown that purified elastin when implanted subdermally in rats undergoes severe calcification. In the present study, we used this elastin implant model to investigate the molecular mechanisms underlying elastin calcification. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…EL-Gel-FGF and EL-Gel samples were implanted subdermally (n = 6 per group per time point) in adult male Sprague Dawley CD rats weighing 250-300g, placed under general anesthesia, as described earlier [11]. Briefly, a 1 cm wide skin incision was made on the back of the rats, and two subcutaneous pouches were created in each rat by blunt dissection.…”
Section: Subdermal Implantation Of Tubular Elastin Scaffoldsmentioning
confidence: 99%
“…EL-Gel-FGF and EL-Gel samples were implanted subdermally (n = 6 per group per time point) in adult male Sprague Dawley CD rats weighing 250-300g, placed under general anesthesia, as described earlier [11]. Briefly, a 1 cm wide skin incision was made on the back of the rats, and two subcutaneous pouches were created in each rat by blunt dissection.…”
Section: Subdermal Implantation Of Tubular Elastin Scaffoldsmentioning
confidence: 99%
“…Each rat received three 30-to 40-mg elastin implants (one per pouch), which were rehydrated in sterile saline 1 to 2 hours before implantation. Four rats were sacrificed by CO 2 asphyxiation at each time point (3,7,14, and 21 days after implantation), and the implants were retrieved along with the surrounding fibrous capsule. One explant from each rat was frozen in OCT (Sakura Finetek, Zoeterwoude, The Netherlands) on dry ice and stored at Ϫ80°C for immunohistochemistry; another explant was frozen on dry ice for protein analysis.…”
Section: Subdermal Implantation Of Elastinmentioning
confidence: 99%
“…4 We have shown earlier that pure elastin undergoes extensive degeneration and calcification when implanted subdermally in juvenile rats 5 and that local delivery of a synthetic MMP inhibitor significantly reduced elastin calcification in the rat subdermal model. 6 Moreover, we have shown that treatment of elastin with aluminum ions before implantation completely abolished elastin calcification by mechanisms that include inhibition of elastolysis by MMPs. 7 These results strongly point to a direct correlation between elastin degradation and calcification.…”
mentioning
confidence: 91%